Corrigendum to “Bi-level programming model for solving distribution center problem: A case study in Northern Thailand's sugarcane management” [Comput. Ind. Eng. 103 (2017) 26–39] (S0360835216304168) (10.1016/j.cie.2016.10.031)) - Supalin Saranwong (2018)
© 2017 Elsevier Ltd The authors regret that the following acknowledgements were omitted in the original article: “This work is supported by Chiang Mai University's Short-Term Research Fellowships Overseas. The authors would also like to thank Assoc. Prof. Dr. Radom Pongvuthithum of CMU's Department of Mechanical Engineering for his programming help, Chaiy Rungsiyakull, also of CMU's Department of Mechanical Engineering, for his technical help, and Ms Wiriya Sungkhaniyom for proofreading this paper.”